New Record of Geoduck Clam Collected from the East Coast of South Korea and Its Reproductive Characteristics - Jeonghoon Han; Jong Guk Kim; O-Nam Kwon; Young-Ung Choi (Journal of Marine Science and Engineering, 2023)
Geoduck clams are important commercial marine resources in Southeast Asia. However, the complete mitochondrial genome of the native geoduck clam in South Korea has not been reported yet. This study reports a geoduck clam collected from the east coast of South Korea. Based on its morphological characteristics and molecular data, the geoduck clam was identified as Panopea sp. belonging to the bivalve family Hiatellidae. We determined the complete mitochondrial genome of this species and investigated the seasonal reproductive pattern for monthly changes in sex ratio, gametogenesis, and reproductive cycle from September 2019 to August 2020. The total length of the complete mitochondrial genome sequence is 16,006 bp, containing 13 protein-coding, 22 transfer RNA, 2 ribosomal RNA, and a control region (D-loop). A molecular phylogenetic comparison with 10 bivalve species showed that the geoduck clam specimen belongs to the family Hiatellidae, clustering with Panopea abrupta Chinese strain, P. generosa, and P. globosa. The gametogenesis of the geoduck clam was identified in six stages by histological analysis. The sex ratio was biased towards males from May 2019 to July 2019, the main spawning activity from the frequency of the gonads with ripe and spent stages occurred from October 2018 to April 2019, and there was no clear pattern of spawning peaks from May to August 2019 with gonads developed asynchronously between both sexes. This is the first study to report new records of the genus Panopea based on the complete mitochondrial genome and to examine the seasonal reproductive pattern of the native geoduck clam Panopea sp. in South Korea, providing valuable information for its sustainable management in South Korea.